Taxation and the financial crisis - Alworth, Julian; Arachi, Giampaolo (Oxford : Oxford University Press, 2012)
This title examines how tax policies contributed to the financial crisis; whether taxation can play a role in the reform efforts to establish a sounder and safer financial system; and the pros and cons of various tax initiatives.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fiscal policy; Global Financial Crisis, 2008-2009.; Taxation